Implementing dietary counselling in family practice for diabetes control and prevention - Abdullah, Marwah Y.; Aljuaid, Atheer M.; Alshamary, Yasmeen W.; Alshammari, Bassam Z.; Alsufyani, Nada M.; Alkhaldi, Rana A.; Alwajaan, Aljoharah M.; Alenazi, Hussam S.; Alshammari, Bandar T.; Alrasheedi, Shadia N.; Alnuwaimees, Khaled F. (International Journal Of Community Medicine And Public Health, 2024)
The importance of dietary counselling in family practice for managing and preventing diabetes is the focal point of this review, highlighting its integral role in chronic disease management. With diabetes increasingly prevalent worldwide, there is a critical need for effective management strategies, with dietary interventions playing a key role. Family practitioners, often the initial point of contact for patients, have a unique opportunity to implement these dietary changes, which are pivotal in influencing diabetes outcomes and averting long-term complications. Despite facing challenges such as limited time and the need for specialized knowledge, dietary counselling in family practice stands as a proactive measure focused on prevention and early intervention. It adopts a patient-centered approach, where dietary habits and preferences are assessed, and personalized, evidence-based advice is provided. The inclusion of dietitians in primary care teams, utilization of technology for support, and advocacy for policy reforms are recommended to enhance the effectiveness of dietary counselling. Despite various obstacles, integrating dietary counselling into routine care remains a significant advantage, promoting healthier lifestyle choices and effectively managing the increasing burden of chronic diseases.